Ethical Performance of Neonatal Nurses in Neonatal Intensive Care Units - Ezati, Arezoo; Shakeri, Fateme; Shahsafi, Fahimeh; Mahdizadeh Shahri, Maryam; Farjami, Mohammad; Varzeshnejad, Maryam (Advances in Nursing & Midwifery, 2022)
Introduction: Lack of adherence to the nursing code of ethics in neonatal wards is usually an issue in hospitals. The present study explored neonatal nurses’ adherence to the nursing code of ethics in the neonatal ward, using the Neonatal Nurses' Ethical Performance Self-Report Questionnaire and the Neonatal Nurses' Ethical Performance Observation Checklist. Methods: In this descriptive study, 132 Nurses from 5 neonatal wards from two pediatric hospitals in Tehran were recruited by census sampling. Results: The results showed that the mean score of the self-report questionnaire (86.12+10.34) and observational checklist (80.98+10.34) was within the desired performance range. The domain of improving the quality of care had the highest score (94.25+3.40) in the self-report questionnaire, and the domain of justice had the highest score (95.00+0) in the observational checklist. The domain of respect for autonomy had the lowest mean score in the self-report questionnaire (64.31+22.22) and the observational checklist (67.50+6.19). There was no significant relationship between the ethical performance score reported by nurses and nurses' demographic variables (P>0.05), and the specific condition of the neonates affected the ethical performance of nurses in neonates' demographic variables (P-value =0.002). Conclusions: The finding showed that, overall, the performance of neonatal nurses regarding ethical codes is desirable.